AN ANALYSIS OF STUDENTS' ENGLISH-INDONESIAN TRANSLATION OF WILLIAM ERNEST HENLEY'S INVICTUS : A case study of students in a translation class at the English Education Department of FPBS UPI - Pradhya, Nada Ardi (2016)
This research investigates how twelve students in a translation class at the English Education Department of FPBS UPI translate Invictus poem by William Ernest Henley into Indonesian. Two main points examined include the strategies applied and the problems encountered by the students in translating the poem. By using a qualitative method with case study design, the data were collected through documents analysis and interviews. Through a textual descriptive analysis, they were classified and analyzed by using Abbasi and Manafi Anari (2004) theory of poetry translation strategies and Hariyanto's theory concerning problems in translating poetry (2003). From the findings of the study, it was found that most of the students apply literal strategy to translate the poem. The other strategies found are blank verse, interpretation, meter imitation, and rhymed translation strategies. Besides, literary and aesthetic problem is the most encountered problem by the students. As a conclusion, it shows that the students often try to maintain the poetic and aesthetic value of the poem rather than maintaining the linguistic feature of the poem. Key terms: Students translation works, poetry translation strategies, poetry translation problems, poetry. Penelitian ini meneliti bagaimana dua belas mahasiswa di kelas penerjemahan di Jurusan Pendidikan Bahasa Inggris FPBS UPI menerjemahkan puisi karangan William Ernest Henley yang berjudul Invictus dari bahasa Inggris ke bahasa Indonesia. Dua hal utama yang dikaji meliputi strategi yang diterapkan oleh mahasiswa dan masalah yang dihadapi oleh mahasiswa dalam menerjemahkan puisinya. Penelitian ini dilakukan dengan menggunakan metode kualitatif dengan desain studi kasus, data dikumpulkan melalui analisis dokumen dan wawancara. Melalui analisa deskriptif secara tekstual, data yang dikumpulkan diklasifikasikan dan dianalisis dengan menggunakan teori strategi penerjemahan puisi dari Abbasi dan Manafi Anari (2004) dan teori dari Hariyanto (2003) yang menyangkut masalah dalam menerjemahkan puisi. Dari temuan penelitian, ditemukan bahwa sebagian besar mahasiswa menerapkan strategi literal untuk menerjemahkan puisinya. Strategi lain yang ditemukan adalah blank verse, interpretation, meter imitation, dan rhymed strategy. Selain itu, masalah mempertahankan makna kesusasteraan dan estetika puisi adalah masalah yang paling banyak dialami oleh mahasiswa. Sebagai kesimpulan, hal ini menunjukkan bahwa mahasiswa sering kali berusaha untuk mempertahankan nilai puitis dan estetika puisinya daripada mempertahankan fitur linguistik dari puisinya. Kata kunci: Karya penerjemahan mahasiswa, strategi penerjemahan puisi,masalah penerjemahan puisi, puisi.